2013
DOI: 10.1128/jvi.03299-12
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Requirement for TIP47 in Human Immunodeficiency Virus Type 1 Envelope Glycoprotein Incorporation

Abstract: Incorporation of the human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins into assembling particles is crucial for virion infectivity. Genetic and biochemical data indicate that the matrix (MA) domain of Gag and the cytoplasmic tail of the transmembrane glycoprotein gp41 play an important role in coordinating Env incorporation; however, the molecular mechanism and possible role of host factors in this process remain to be defined. Recent studies suggested that Env incorporation is mediated by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…A second highly conserved YW motif lies just C-terminal at position 802 and was previously implicated in Env incorporation and in linking Env to TIP47 (19). However, the connection between Env and TIP47 has not been supported in other studies (20).…”
Section: Discussionmentioning
confidence: 55%
“…A second highly conserved YW motif lies just C-terminal at position 802 and was previously implicated in Env incorporation and in linking Env to TIP47 (19). However, the connection between Env and TIP47 has not been supported in other studies (20).…”
Section: Discussionmentioning
confidence: 55%
“…While the presence of Env is necessary for cell-free infection, the structure of the tail or its ability to recruit a trans-acting factor(s) may influence infection levels of cell-free but not cell-to-cell HIV-1. A recent study by Checkley et al found that knockdown of TIP47 in Jurkat cells did not alter envelope incorporation, virus production, or infectivity of cell-free HIV particles (65), indicating that TIP47 may not be critical to the originally described phenotype of reduced Env incorporation and cell-free infectivity. While the role of TIP47 as a trans-acting factor involved in Env packaging has been called into question, our results are consistent with studies describing these LLP-3 amino acid residues as important for infection (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…This myristate and a stretch of highly basic amino acids at the N-terminal end of MA play important roles in Gag targeting to the plasma membrane. In addition, interactions of MA with the cytoplasmic tail of gp41, directly or indirectly through a yet to be determined host factor (81), are critical for efficient incorporation of functional Env into budding virus particles (32,33,71,72). Furthermore, recent studies have also suggested that Env trimers on the HIV-1 virion are reorganized to cluster prior to engagement with CD4, a reorganization process triggered by internal core maturation (82).…”
Section: Discussionmentioning
confidence: 99%